Analisis Halal Supply Chain Management Produk Kosmetik Halal Terhadap Tingkat Kepuasan Generasi Milenial di Kabupaten Deli Serdang - Indah Cahya Sagala; Fauziah Rahman; Sucitra Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research aims to determine the influence of halal supply chain management for halal cosmetic products on millennial generation consumer satisfaction in Deli Serdang Regency. The type of research used is quantitative associative which aims to determine the influence between the independent variable and the dependent variable. The type of data used is primary data in the form of a questionnaire distributed via social media. The population in this study is the entire millennial generation who use halal cosmetic products in Deli Serdang Regency. The location for Deli Serdang Regency was chosen because Deli Serdang is the regency with the largest population of the millennial generation and Muslims in Sumatera Utara Province. Sampling was determined based on Malhotra's theory so that a total sample of 160 samples was obtained. The results of this research state that halal supply chain management has a positive and significant effect on millennial generation consumer satisfaction in Deli Serdang . With this research, it is hoped that cosmetic companies or manufacturers can pay more attention to the halalness of a product, from ingredients, manufacture to distribution of cosmetics to consumers while still using Islamic provisions or in accordance with sharia.